2004
DOI: 10.1002/mabi.200300123
|View full text |Cite
|
Sign up to set email alerts
|

Polypyrrole Thin Films Formed by Admicellar Polymerization Support the Osteogenic Differentiation of Mesenchymal Stem Cells

Abstract: The objective of this study was to evaluate the attachment, proliferation, and differentiation of rat mesenchymal stem cells (MSC) toward the osteoblastic phenotype seeded on polypyrrole (PPy) thin films made by admicellar polymerization. Three different concentrations of pyrrole (Py) monomer (20, 35, and 50 x 10(-3) M) were used with the PPy films deposited on tissue culture polystyrene dishes (TCP). Regular TCP dishes and PPy polymerized on TCP by chemical polymerization without surfactant using 5 x 10(-3) M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
94
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(95 citation statements)
references
References 46 publications
0
94
0
1
Order By: Relevance
“…(43)(44)(45) Cultured cells do not adhere to the substrate with well-like pores. (46) The field emission SEM images depicted the well-like structure in wildtype calvarial bone.…”
Section: Col9a1mentioning
confidence: 99%
“…(43)(44)(45) Cultured cells do not adhere to the substrate with well-like pores. (46) The field emission SEM images depicted the well-like structure in wildtype calvarial bone.…”
Section: Col9a1mentioning
confidence: 99%
“…But in the same situation, lesions of grafted animals were seen as dark hypointense areas. Compared to control rats, the lesions gathering by MSCs in grafted animals become considerably smaller, which suggested a positive effect of the MSCs on lesion repair [55].Moreover, several successful applications of MR tracking can be found in other organs, such as heart [56], liver [57], kidney [58] and pancreatic islets [59]. It is reported that bronchioalveolar stem cells (BASCs) were successfully isolated from the murine lung using magnetic nanoparticle-based surface-enhanced Raman spectroscopic dots (M-SERS Dots) [60].…”
Section: Figure1mentioning
confidence: 99%
“…For example, Castano, et al focused on the thickness of polypyrrole films and their potential as a biocompatible material for rat MSCs [106]. Others have investigated the potential of electrospun porous scaffolds of randomly oriented 500 nm to 900 nm diameter nanofibers for cartilage repair [107][108]. Nanofibrous structures can favorably modulate osteoblast, osteoclast, and fibroblast activities toward implant and/or scaffold materials [109].…”
Section: Application Of 3d Nanostructures In Stem Cell Tissue Engineementioning
confidence: 99%
“…By incorporating polypyrrole (PPy) into the fibers, we hypothesize that it would improve their mechanical properties as well as introduce electroactivity to the fibrous scaffold. Polypyrrole is a well-studied biomaterial for numerous applications in tissue engineering [8][9][10]. The monomer pyrrole does not possess a net charge, therefore rendering it suitable for PEC fabrication.…”
Section: Introductionmentioning
confidence: 99%